Efficient syntheses of new polyhydroxylated 2,3-diaryl-9h-xanthen-9-ones - Santos, Clementina M.M. (2011)
A large number of hydroxylated 2,3-diaryl-9H-xanthen-9- ones have been synthesised by two different approaches, starting either from 3-bromo-2-methyl-4H-chromen-4-one or from (E)-3-bromo-2-styryl-4H-chromen-4-ones. The former method involves Heck reactions between 3-bromo-2-methyl- 4H-chromen-4-one and styrenes, leading to (E)-2-methyl-3- styryl-4H-chromen-4-ones; these condensed with benzaldehyde to give (E,E)-2,3-distyryl-4H-chromen-4-ones, which led to the desired 2,3-diaryl-9H-xanthen-9-ones under reflux in 1,2,4-trichlorobenzene. 3-Bromo-2-styryl-4H-chromen-4- ones were obtained either by aldol condensations between 3-bromo-2-methyl-4H-chromen-4-one and benzaldehydes, or through Baker–Venkataraman rearrangements of 2-acetylphenyl cinnamates, followed by one-pot bromination/ cyclisation with phenyltrimethylammonium tribromide. The 2,3-diaryl-9H-xanthene-9-ones were obtained in one-pot transformations involving Heck reactions between (E)-3- Introduction Xanthones constitute one of the major classes of naturally occurring oxygen-containing heterocyclic compounds containing dibenzo-γ-pyrone rings.[1] They occur in two major plant families, Guttiferae and Gentianaceae, and also in some families of fungi and lichens.[2,3] Natural derivatives can be hydroxylated, methoxylated or prenylated, among other possibilities; the parent compound xanthone itself is not known as a natural product.[3,4] The presence of aryl groups on the xanthone core has only been reported for a few synthetic derivatives, and as far as we know the literature had never presented the synthesis of xanthones featuring 2,3-diaryl moieties before our work.[5,6] Over the last decades these substances have been extensively studied not only because they participate in several biological functions but also as a consequence of their remarkable antifungal,[7–9] anti-inflammatory,[10,11] antimalarial[ 12–14] and antitumour activities,[15,16] and even as promising antioxidant agents.[17–19] Structure–activity stud- [a] Department of Vegetal Production and Technology, Escola Superior Agrária de Bragança, 5301-855 Bragança, Portugal Fax: +351-273-325405 E-mail: clems@ipb.pt [b] Department of Chemistry & QOPNA, University of Aveiro, 3810-193 Aveiro, Portugal Fax: +351-234-370084 E-mail: artur.silva@ua.pt © 2009 Wiley-VCH Verlag GmbH 2642 & Co. KGaA, Weinheim Eur. J. Org. Chem. 2009, 2642–2660 bromo-2-styryl-4H-chromen-4-ones and styrenes, followed by electrocyclisation and oxidation processes. The 2,3-diaryl- 3,4-dihydro-9H-xanthene-9-one intermediates were also isolated under these conditions, and so when 5-methoxy-2-styryl- 4H-chromen-4-ones were used as starting materials the 1-hydroxy-6,7-diaryl-9H-xanthene-9-ones were also observed. The second method is a general one, because it allowed the synthesis of a great number of 2,3-diaryl-9Hxanthen- 9-ones with several substitution patterns, whereas the first one is limited to certain derivatives. The last step in the synthesis of hydroxylated 2,3-diaryl-9H-xanthen-9-ones was the cleavage of the hydroxy protecting groups with boron tribromide. The structures and stereochemistry of all new compounds were established by NMR studies.